Transpiration of the 'Rebula' cuttings (Vitis vinifera L.) grafted on three different rootstocks (Vitis sp.) - Primož LAVRENČIČ; Paolo SIVILOTTI; Enrico PETERLUNGER (Acta Agriculturae Slovenica)
The purpose of the investigation was to determine the use of water in grafted vines (Vitis vinifera L.) in dependence on the vine (Vitis sp.) rootstocks. The local vine variety 'Rebula' was grafted on three different rootstocks (Vitis sp.): (1) on the 'Rebula' (Vitis vinifera L.) vine itself, (2) on the rootstock 196/17 Castel' [(Vitis vinifera 'Mourvèdre' x Vitis rupestris '1202 Couderc') x Vitis riparia 'Gloire'] and (3) on the rootstock 'Börner' (Vitis riparia x Vitis cinerea). Daily transpiration was calculated as a difference in the pot mass between the day of measurement and the previous day. Daily differences in the use of water were compared with leaf area and meteorological data (temperature, duration of sun light). Stem water potential (SWP) and, at the end of the trial, leaf area and mass of individual parts of plant (roots, shoot) were determined using destructive method. The dynamics of water used per leaf area unit showed the trend of reduction and the response to the changing meteorological conditions. No statistically significant differences in SWP, leaf area and water used were noticed between rootstocks, however, they existed in the final mass of shoot and roots.